2009
DOI: 10.1007/s11239-009-0419-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of distal embolization on myocardial perfusion and survival among patients undergoing primary angioplasty with glycoprotein IIb–IIIa inhibitors: insights from the EGYPT cooperation

Abstract: Even though primary angioplasty is able to obtain TIMI 3 flow in the vast majority of STEMI patients, epicardial recanalization does not guarantee optimal myocardial perfusion, that remain suboptimal in a relatively large proportion of patients. Large interest has been focused in recent years on the role of distal embolization as major determinant of impaired reperfusion. The aim of the current study was to investigate in a large cohort of STEMI undergoing primary angioplasty with Gp IIb-IIIa inhibitors the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Patients with distal embolization are more likely to have reduced myocardial blush grade and TIMI reperfusion grade after angioplasty, suggesting worse reperfusion [29, 30]. Some previous studies found increased mortality rates at 1- and 5-year follow-up of patients with distal embolization and an increased risk of heart failure regardless of the use of distal protection [9, 3133].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with distal embolization are more likely to have reduced myocardial blush grade and TIMI reperfusion grade after angioplasty, suggesting worse reperfusion [29, 30]. Some previous studies found increased mortality rates at 1- and 5-year follow-up of patients with distal embolization and an increased risk of heart failure regardless of the use of distal protection [9, 3133].…”
Section: Discussionmentioning
confidence: 99%
“…Davies MJ et al found that atheroma is at high risk for rupture when more than 40% of the plaque consists of lipid/NC (31). The meta-analysis by Ding S et al revealed that compared with patients with normal flow, significantly higher absolute necrotic core volume and dense calcium were found in ACS patients with distal embolization (32,33). The HORIZONS-AMI Trial showed that the larger the attenuated plaque is, the greater the likelihood of no-reflow is (24).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors have been shown to impact on such occurrence, such as diabetes mellitus, acute clinical presentation and complex angiographical lesions. In fact, the release of prothrombotic factors can cause microvascular thrombosis, platelet plugging, vasoconstriction and slow-flow or no-reflow phenomenon [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%